PERAN TEKNOLOGI BLOCKCHAIN DALAM MENINGKATKAN TRANSPARANSI PEMERINTAHAN - Axelon S Renyaan; Loso Judijanto (CV. Adiba Aisha Amira, 2025)
This study aims to examine the role of blockchain technology in improving government transparency through a literature review approach. Blockchain is a decentralised digital recording system with key characteristics such as transparency, security, and data immutability, making it capable of addressing various classic problems in government bureaucracy, such as corruption, data manipulation, and administrative inefficiency. Through literature analysis, this study found that blockchain implementation can create a record-keeping system that is openly auditable by the public, promote bureaucratic efficiency through the automation of administrative processes using smart contracts, and enhance public trust in the government. However, behind these significant opportunities lie challenges that must be addressed, such as cultural resistance, infrastructure limitations, the need for clear regulations, and data privacy protection. Therefore, cross-sector collaboration, strengthened regulations, and education are key to the successful implementation of blockchain to achieve more transparent, efficient, and accountable governance in the future.